(untitled) (Academia Journal of Medicine, 2025)
Low Level Laser Therapy (LLLT) has emerged as a promising adjunct treatment for periodontal diseases, characterized by its anti-inflammatory and analgesic effects. This review assesses the efficacy of LLLT in managing periodontal conditions, high lighting its mechanisms of action, clinical applications, and outcomes. Studies sug gest that LLLT promotes tissue healing, reduces pain, and enhances the effective ness of conventional periodontal treatments. Furthermore, the review discusses the optimal parameters for laser application, including wavelength, energy density, and duration. Through an analysis of current clinical trials, this review aims to provide a comprehensive understanding of LLLT as a viable option in periodontal therapy.